Theodoros Chiotis’s Atemporal Crossroads: A Review of limit.less_an assembly of the sick - Dylan Williams (Janeway JS, 2019)
A review of Theodoros Chiotis's new poem limit.less_an assembly of the sick, published by Litmus in 2017.